2018
DOI: 10.2136/vzj2017.03.0056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mucilage on Rhizosphere Hydraulic Functions Depend on Soil Particle Size

Abstract: Mucilage secreted by roots alters hydraulic properties of soil close to the roots. Although existing models are able to mimic the effect of mucilage on soil hydraulic properties for specific soils, it has not yet been explored how the effects of mucilage on macroscopic soil hydraulic properties depend on soil particle size. We propose a conceptual model of how mechanistic pore-scale interactions of mucilage, water, and soil depend on pore size and mucilage concentration and how these pore-scale characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 48 publications
5
76
0
7
Order By: Relevance
“…The latter is explained by the maintained connectivity of the liquid phase during drying, which enables film flow at low water potentials. This result shows that the maintained connectivity of the liquid phase during drying counteracts the expected decrease in permeability caused by the shrinkage of the polymer matrix (Kroener et al, 2018).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The latter is explained by the maintained connectivity of the liquid phase during drying, which enables film flow at low water potentials. This result shows that the maintained connectivity of the liquid phase during drying counteracts the expected decrease in permeability caused by the shrinkage of the polymer matrix (Kroener et al, 2018).…”
Section: Resultsmentioning
confidence: 79%
“…To what extent the emerging matrix augments the water retention of soils is still not known. Kroener et al (2018) reported greater water retention of mucilage in fine‐ than in coarse‐textured soils. The pronounced water retention in fine‐textured soils can be explained by the higher specific surface area of these soils and the amplified entanglement of polymers with the soil particles, which favors the formation of the polymer matrix across the pore space.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil columns were saturated with water for a period of 48 h by capillary rise, and subsequently a constant water level difference of 2 cm was established between the top and the bottom of the samples, and water outflow was determined. This information (outflow [cm 3 s −1 ], the geometry of soil, and established pressure gradient [cm]) was used to calculate the saturated hydraulic conductivity of the soil ( K s , cm s −1 ) based on Darcy's equation (Kroener et al, 2018). The van Genuchten–Mualem equation was used to parameterize the unsaturated hydraulic conductivity of soil: K(normalΞ)=KnormalsnormalΘnormalλ[ 1−(1−normalΘ1/m)normalm ]2 where K (Ξ) is the hydraulic conductivity of the soil as a function of soil water content (cm s −1 ), λ is a unitless fitting parameter describing the tortuosity of the flow path, and m = 1 – 1/ n .…”
Section: Methodsmentioning
confidence: 99%
“…It is proposed that bioadhesive mucilage components of exudates are important factors, along with root hairs, in the formation of cylinders of soil around roots known as rhizosheaths. It appears that this will involve differing impacts on soil aggregation through varied viscosities and surface properties, on drying/wetting cycles and the potential for hydrophobicity of mucilage after drying and binding properties in general, including the sequestering of heavy metals (Ray et al, 1988;Watt et al, 1994;Dennis et al, 2010;Naveed et al, 2017;Kroener et al, 2018). Rhizosheath bioengineering by some grass species during periods of drought has been observed, where the grasses increased the thickness of their rhizosheaths (Hartnett et al, 2012).…”
Section: Root Exudates Bioengineer Rhizospheres For Sustained Resourcmentioning
confidence: 99%